Memórias entrelaçadas e histórias de docência no ensino multisseriado em Inhangapi (PA) - CARMO, Maria de Fátima Ferreira do (2019)
The present work is based on concerns and experiences in more than thirty years of acting as a teacher in multi-serials classes in the municipality of Inhangapi-PA. It has a problem: what do the teachers' reports say about their memories of teaching experiences in multi-series classes in the municipality of Inhangapi / PA? The general objective is to analyze the teachers' reports about their memories of teaching experiences in multi-series classes in the municipality of Inhangapi / PA. The specific objectives are: to present fundamental theoretical-conceptual notions to involve the topic under discussion; to discuss the historical conditions of multi-seriado teaching in the Amazon and to analyze the reports of the memories of teaching experiences of teachers of multi-serials classes in the municipality of Inhangapi / PA. Methodological basis was sought in the qualitative research and the methodological instrument chosen for the accomplishment of the field work was the on-site observation through a proposed questionnaire, which was analyzed from the dialogue with some theorists as: Hage (2005, 2006, 2014) , Almeida (2018), Bosi (1994), Escudeiro (2014), Freire (1996), Kramer (2010), among others. The subjects involved were two teachers of the public enno and multi-series classes. In view of the obtained results, we can see that the report of the teaching memories allows us to understand the teaching and learning process through the presented context, making an analogy with the present days and thus taking over this process in a systematic way.